Green Gasification Technology for Wet Biomass - W. H. Chong; J. W. Leong; J. H. Leong; I. Mohammad Halim Shah (Jurnal Rekayasa Kimia & Lingkungan, 2010)
The world now is facing two energy related threats which are lack of sustainable, secure and affordable energy supplies and the environmental damage acquired in producing and consuming ever-increasing amount of energy. In the first decade of the twenty-first century, increasing energy prices reminds us that an affordable energy plays an important role in economic growth and human development. To overcome the abovementioned problem, we cannot continue much longer to consume finite reserves of fossil fuels, the use of which contributes to global warming. Preferably, the world should move towards more sustainable energy sources such as wind energy, solar energy and biomass. However, the abovementioned challenges may not be met solely by introduction of sustainable energy forms. We also need to use energy more efficiently. Developing and introducing more efficient energy conversion technologies is therefore important, for fossil fuels as well as renewable fuels. This assignment addresses the question how biomass may be used more efficiently and economically than it is being used today. Wider use of biomass, a clean and renewable feedstock may extend the lifetime of our fossil fuels resources and alleviate global warming problems. Another advantage of using of biomass as a source of energy is to make developed countries less interdependent on oil-exporting countries, and thereby reduce political tension. Furthermore, the economies of agricultural regions growing energy crops benefit as new jobs are created.